Al-Tarbiyah wa Thuruqu al-Tadris: Strategi Pendidikan Islam untuk Membentuk Generasi Unggul - Nurmawati, Nurmawati; Suhaidi, Suhaidi; Taufiqurrahman, Taufiqurrahman; Ainin, Nadia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Islamic education plays a central role in shaping generations that are morally, intellectually, and spiritually excellent. This literature review aims to investigate various strategies and methods within Al-Tarbiyah wa Thuruqu al-Tadris (Education and Teaching Methods) in the context of Islam, with the ultimate goal of forming a generation capable of facing the challenges of the modern era. In this research, the scholar explores literature related to Islamic education, particularly focusing on Al-Tarbiyah (education) and Thuruqu al-Tadris (teaching methods) as key instruments. The research approach includes the analysis of classical texts, contemporary literature, and the thoughts of Islamic education scholars. The research findings highlight the importance of understanding the principles of tarbiyah in Islam, along with the implementation of innovative teaching methods that align with the demands of the times. Educational articles, textbooks, and empirical research related to this theme are also analyzed to gain a more comprehensive insight. This study illustrates the alignment between Islamic education and character formation, as well as how thuruqu al-tadris can be effectively applied. These findings can contribute to the development of better Islamic education strategies, with the hope of shaping a generation that excels not only academically but also possesses moral integrity and spiritual resilience in navigating the dynamics of the modern world.